THE IMPACTS OF NGOS AND VOLUNTARY ORGANIZATION - EBOA, Adolf Diange (The Graduate School, Ajou University, 2010)
Health is the basics for life. We have to therefore direct our ways of living, for the greater achievements？ of this life. The ？human will？ plays a great role for this process of life accomplishments and its pleasures. Individual responsibility towards sex remains one of the fundamental as concerns HIV/AIDS. The Government of Cameroon is strongly involved in the provision of health facilities？, to her citizens. HIV/AIDS Health sector of the Ministry of Public health has being of great concern. The Government has as strategic plan, the National AIDS Control committee to be concern with the reduction of HIV/AIDS Prevalence rate. This has been running from the year 2000 and is expected to match with the Millennium Development Goals by 2015. The plan runs in three phases; 2000~2005 for phase one, 2006~2010 for phase two and finally 2011~2015 for phase three. Phase one was successful with a drop from 11.6% to 5.6%. Unfortunately, the second phase was a failure, because the results show only a reduction from 5.6% to 5.1%. This thesis examines the government plans against HIV/AIDS, and also looks into two NGOs in South West Region Cameroon, as case study. These thesis identify reasons for the failure and give possible recommendations, which will in turn contribute for the current running third phase of the Government Strategic plan.
학위논문(석사)--아주대학교 국제대학원--NGO학과,2010. 8